SERVICE QUALITY AND CUSTOMER LOYALTY: THE ROLE OF SATISFACTION AND TRUST IN INDONESIAN SHARIA BANK - Novitasari, Maya; Amah, Nik; Ayera, Anissa; Aziz, Ahmad; Gunardi, Ardi (Jurnal Riset Bisnis dan Manajemen, 2024)
This study determines the effect of service quality on customer loyalty with satisfaction and trust as mediating variables in Indonesia sharia banks during the Covid-19 pandemic period. This study used 300 respondents of sharia bank customers in Indonesia. The data were analyzed using a partial least square with the SmartPLS 3.0 analysis tool. Service quality has a positive effect on customer loyalty, service quality has a positive effect on customer satisfaction, service quality has a positive effect on trust, satisfaction has a positive effect on customer loyalty, trust has a positive effect on customer loyalty, satisfaction is able to mediate the effect of service quality on customer loyalty, and trust is able to mediate the effect of service quality on loyalty. This study adopts two mediating variables, namely satisfaction and trust in the effect of service quality on customer loyalty. The results present partial mediation of satisfaction on the influence of service quality on customer loyalty and partial mediation of trust on the influence of service quality on customer loyalty.